Simulation of oil spill scenarios in the South-East coastal zone of Viet Nam - Du Van Toan; Nguyen Quoc Trinh (Petrovietnam Journal, 2013)
The risk of environmental disasters related with the spilling of oil products into the sea forces the development of high-quality oil spill simulation and prediction system. In an worst-case scenario, only 48 hours after an oil spill occurs, with the speed of the north-east wind being 7 m/s, the entire Southeast coastal area of Viet Nam will be affected, resulting in great economic losses and serious damages to the marine environment. The article presents the method of simulation of the oil spreading and fate in the sea that integrates the results of meteorological, oceanographic and oil spill modeling. The oil spill numerical simulation system could facilitate more effective and timely short term planning of oil spill recovery operations.